The effects of historical land use on plant diversity in semi-natural grasslands - Kumlander, Elisabeth (SLU/Dept. of Ecology, 2022)
During the last two centuries, large-scale administrational and technological reforms have drastically changed the agricultural landscape in Sweden. The meadows and semi-natural grasslands that once played a central role in the agricultural landscape have been reduced with up to 95%. This has entailed large losses of habitat for vascular plants that rely on traditional management practises, and a decrease in the overall plant species richness of managed landscapes. Yet, traces of historical land use, so-called legacy effects, often remain and influence the present-day distribution of plants. How such historical land use affects the species richness we have today and how these changes in land use affect the diversity of vascular plants are investigated here. In this study, I inventoried a total of 97 different grassland and afforested grassland plots in two locations and related the plant species richness and specialist plant occurrence to historical land uses with the help of historical land-use maps obtained from a project by Cousins (2009). The results indicate that legacy effects of historical land use influence present-day plant communities but that these vary across the different locations, probably due to site-specific effects. The results seem to be contradictory to each other in the two locations that were included.